Volunteering in the Tourism Industry of the Republic of Kazakhstan - BAIMBETOVA, Assel; MUTALIYEVA, Lyailya; KENZHIN, Zhaxat; SEIDUALIN, Darken; TLEUBERDIYEVA, Saltanat; MUSSINA, Kamshat (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021, 2021)
The article deals with the specifics of volunteering in tourism industry of the Republic of Kazakhstan. Of particular importance is the problem of developing volunteering movement in tourism sphere of Kazakhstan, which is in the process of formation and integration. Developing volunteering in tourism for Kazakhstan is an important factor in ensuring its growth, forming positive image, creating favourable conditions for the tourism business, increasing awareness about the country, and improving the well-being of its people. The relevance of the topic is that among various directions of tourism development, volunteering has a powerful, but underestimated resource for creating positive image of a country, solving social, economic and environmental problems, improving the quality of tourism services provided, helping the population in emergencies, different life situations, which may occur in the course of a travel. The purpose of this work is to analyse the theoretical aspects regarding the role of volunteering in tourism development, identifying its trends and problems, as well as developing scientifically based applied recommendations to increase the attractiveness of volunteering in tourism. The results obtained in the course of the study can be implemented in fostering volunteering development in tourism sphere.